Child-Friendly Digital Literacy at TK/RA Tadika Adnani: A Collaborative PIAUD Initiative - Sovia Ikhwani Putri (PT Agung Media Publisher, 2024)
The integration of digital literacy into early childhood education is increasingly vital in today’s technology-driven world. This study explores the collaborative efforts of PIAUD students from STAIN Mandailing Natal in developing a child-friendly digital literacy platform at TK/RA Tadika Adnani, aimed at enhancing educational outcomes and community engagement. This community service project utilized a structured, multi-phase approach. It began with a needs assessment and planning phase, followed by the formation of specialized teams focusing on data collection, content development, website design, and programming. The project also integrated teaching activities at the school, where students applied interactive methods alongside the website development. The final phase involved implementing the website and gathering feedback from the community to evaluate its effectiveness. The project culminated in the creation of a user-friendly and informative website for TK/RA Tadika Adnani, featuring comprehensive school information, an online registration form, and multimedia galleries. The teaching activities conducted by the students led to observable improvements in the children’s cognitive, social, and emotional development. The initiative successfully addressed the need for a digital platform in early childhood education, demonstrating how collaboration and technology can enhance educational delivery and outreach. The project also provided PIAUD students with practical experience in applying their knowledge in real-world settings. This collaborative effort not only improved the school’s digital presence but also enriched the learning experiences of both the children and the students involved. The project serves as a model for integrating digital literacy into early childhood education through community-based initiatives.